PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN: Studi Kasus Perusahaan Sub Sektor Otomotif dan Komponen - Defi Islamiati, - (2019)
This study aims to determine the effect of Capital Structure which is proxied by Debt to Equity Ratio (DER), Company Size proxied by Natural Asset Logarithm, and Profitability which is proxied by Return On Equity (ROE) on Firm Value with Price to Book Value proxy (PBV ) The population in this study is the automotive sub-sector manufacturing companies and components listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The sample selection technique used was purposive sampling and obtained 6 automotive sub-sector companies and components with a five-year study period so that 30 sample units were obtained in this study. Data analysis was performed using Microsoft Excel 2010 and hypothesis testing in this study used Panel Data Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the study partially show that, (1) capital structure (DER) does not have an effect on firm value (PBV), (2) firm size (SIZE) has a positive significant effect on firm value (PBV), (3) profitability ( ROE) has a significant positive effect on firm value (PBV).